Subcutaneous drainage using Beck’s technique for massive subcutaneous emphysema in a pediatric patient: a case report - Mattos Navarro, Pablo (2021)
Several therapies are used for the management of subcutaneous emphysema in adults, but no reference to subcutaneous drainage using Beck’s technique has been found in pediatric patients. This is the clinical case of a 14-year-old female patient who presented a blunt force trauma that resulted from a ten-meter-high fall. On admission, she was unconscious and developed respiratory distress syndrome, thus mechanical ventilation was indicated. Seven days later, subcutaneous emphysema occurred, and a fenestrated angiocatheter was inserted using Beck’s method. At 24 hours, the emphysema was reduced in the upper chest and face, and, at 72 hours, complete resolution was observed.